TWO NEW VARIETIES OF BEGONIA HOOVERIANA FROM SULAWESI - DEVI ALVITASARI; TATIK CHIKMAWATI; DORLY Dorly; RUGAYAH RUGAYAH; WISNU HANDOYO ARDI (BRIN Publishing (Penerbit BRIN), 2024)
ARDI, W. H. & THOMAS, D. C. 2022. Synopsis of begonia (begoniaceae) from the northern arm of Sulawesi and Sangihe island, Indonesia, including three new species. Edinb. J. Bot 405: 1–50. DOORENBOS, J., SOSEF, M. S. M. & DE WILDE, J. J. F. E. 1998. The sections of Begonia including descriptions, keys and species lists (Studies in Begoniaceae VI). Agric Univ Wageningen Pap 98: 1–266. DUISTERMAAT, H. 1987. A revision of Oryza (Gramineae) in Malesia and Australia. Blumea 32: 157–193. HARTUTININGSIH, M. S., ARDAKA, I. M. & MUSTAID, S. 2007. Flowering Period of 22 Species of Wild Begonias in Bali Botanic Garden. Biodiversitas 8(3): 192–196. HUGHES, M. 2006. Four new species of Begonia (Begoniaceae) from Sulawesi. Edinb J Bot 63(2&3): 191–199. BRC. 2023. Begonia Resource Centre. Faciliated by the Royal Botanic Gardens, Kew. http://padme.rbge.org.uk/begonia. (Accessed 13 December 2023). LIN C. W., THOMAS, D. C., ARDI W. H. & PENG, C. I. 2017. Begonia ignita (sect. Petermannia, Begoniaceae), a new species with orange flowers from Sulawesi, Indonesia. Gard Bull Singapore 69(1): 89–95. MOONLIGHT, P. W., ARDI, W. H., PADILLA, L. A., CHUNG, K. F., FULLER, D., GIRMANSYAH, D., HOLLANDS, R., MAHARDIKA, A., JARA-MUÑOZ, A., KIEW, R., KUMARAGE, L., LEONG, W. C., LIU, Y., O’CONNOR, M., PENG, C. I., PÉREZ, Á. J., PHUTTHAI, T., PULLAN, M., RAJBHANDARY, S., REYNEL, C., RUBITE, R. R., JULIA, S., SCHERBERICH, D., SHUI, Y. M., TEBBITT, M. C., THOMAS D. C. & HUGHES, M. 2018. Dividing and conquering the fastest growing genus: Towards a natural sectional classification of the mega-diverse genus Begonia (Begoniaceae). Taxon 67(2): 267–323. MUNAWAROH, E. & HARTUTININGSIH, M. S. 2018. Upaya konservasi eks-situ famili Begoniaceae dari taman Nasional Bukit Barisan Selatan di Kebun Raya Liwa, Kabupaten Lampung Barat, Provinsi Lampung. Florea 5(1): 44–52. THOMAS, D. C. & ARDI, W. H. 2020. Synopsis of Begonia (Begoniaceae) of southwest Sulawesi and the Selayar Islands, Indonesia, including one new species. Phytotaxa 437(2): 73–96. SBDP. 2023. Sulawesi Begonia Data Portal. Faciliated by the Flora Malaisiana. https://portal.cybertaxonomy.org/flora-malesiana-prospective/node/1 (Accessed 10 December 2023). WIRIADINATA, H. 2013. A New Species of Begonia (Begoniaceae) From South Sulawesi, Indonesia. Reinwardtia 13(5): 445–448.